Ethylene Response of Plum ACC Synthase 1 (ACS1) Promoter is Mediated through the Binding Site of Abscisic Acid Insensitive 5 (ABI5) - Avi Sadka; Qiaoping Qin; Jianrong Feng; Macarena Farcuh; Lyudmila Shlizerman; Yunting Zhang; David Toubiana; Eduardo Blumwald (Plants, 2019)
The enzyme 1-amino-cyclopropane-1-carboxylic acid synthase (ACS) participates in the ethylene biosynthesis pathways and it is tightly regulated transcriptionally and post-translationally. Notwithstanding its major role in climacteric fruit ripening, the transcriptional regulation of ACS during ripening is not fully understood. We studied fruit ripening in two Japanese plum cultivars, the climacteric Santa Rosa (SR) and its non-climacteric bud sport mutant, Sweet Miriam (SM). As the two cultivars show considerable difference in ACS expression, they provide a good system for the study of the transcriptional regulation of the gene. To investigate the differential transcriptional regulation of ACS1 genes in the SR and SM, their promoter regions, which showed only minor sequence differences, were isolated and used to identify the binding of transcription factors interacting with specific ACS1 cis-acting elements. Three transcription factors (TFs), abscisic acid-insensitive 5 (ABI5), GLABRA 2 (GL2), and TCP2, showed specific binding to the ACS1 promoter. Synthetic DNA fragments containing multiple cis-acting elements of these TFs fused to β-glucuronidase (GUS), showed the ABI5 binding site mediated ethylene and abscisic acid (ABA) responses of the promoter. While TCP2 and GL2 showed constant and similar expression levels in SM and SR fruit during ripening, ABI5 expression in SM fruits was lower than in SR fruits during advanced fruit ripening states. Overall, the work demonstrates the complex transcriptional regulation of ACS1.